(3eMGW HGdeQVi GdfaSjjf (B:s (3cja JMej faSc ef JdGYH hGSJZdGd GdBNQjf (B/s - (3EQjcShf, JheGS,s 1965-; (3MSf, CMeOs; (3EQjcShf, JheGS,s 1965-. ([(3GdbGgQI(B] :s (3YUjQ GdcJH ddfTQ hGdJhRjY,s, 2022)
(3GSJQGJjLjGJ HSjWI ddJYGed eY GdCTNGU GdNWjQjf(B. (3aj GdcJGH GdCcKQ eHjYG Ydi eSJhi GdYGde (B"(3eMGW HGdMebi(B"(3, ZjQ JheGS EQjcShf GdWQjbI GdJj jJhGUd HgG GdedGjjf hjJaGYdhf eY HYVge HYVG HGSJNOGe fXGe OjSc GdHSjW dCfeGW GdSdhcjGJ HCdhGfg GdCQHYI(B. (3hdcf eGPG Yf GdCTNGU GdPjf dG jfWHb Ydjge Pdc GdJUfja? aj cJGH eMGW HGdeQVi GdfaSjjf, jcTa EQjcShf Yf eNGWQ GdJYGed eY gDdGA GdCTNGU(B. (3hJUd JbOjQGJg Edi Cf (B2 % (3ef ScGf GdYGde eNJdhf faSjG jNGdahf cd JhbYGJfG GdSdhcjI; jaJbQhf Edi GdEMSGS HGdTabI hGdJYGWa, hjejdhf Edi GdJdGYH HGdBNQjf HdG fOe ef CLd NOeI CgOGage(B. (3jJSe GdeNJdhf faSjG HbhI GdedGMXI, hGdGSJZdGdjI, hdf jJQOOhG aj JOejQ MjGJc GdegfjI Ch GdYGFdjI aj ZeVI Yjf(B. (3aj gPG GdcJGH, SJLOhf GdCOhGJ GdJj JMJGLhf EdjgG dMeGjI CfaSce hCMHGFce ef Jdc GdeNGWQ(B.s
(3GdfGTQ GdCUdj (B: (3JheGS EQjcShf(B.s
(3hQO CYdi UaMI GdZdGa (B: (3ef GdcJH GdCcKQ eHjYG Ydi eSJhi GdYGde(B.s
(3JObjb dZhj (B: (3CMeO EHQGgje ; JfSjb OGNdj (B: (3eYJR MSfjf Ydjs
(3HHdjhLQGajI (B: (3UaMI (B325-326.s
Keywords: (3GdSdhc (B((3Yde faS(B)s; (3GdTNUjIs -- (3LhGfH faSjIs; (3GdTNUjIs -- (3LhGfH GLJeGYjIs; (3Yde GdfaS GdGLJeGYjs